Intraplacental choriocarcinoma and spontaneous fetomaternal hemorrhage: Uncovering diagnostic clues in a challenging case - Wang, Li; Li, Xuri; Bai, Dongfang; Du, Ran; Lu, Linna; Li, Yujie; Wang, Xiuyu (Frontiers in Oncology, 2025)
BackgroundIntraplacental choriocarcinoma (IC) is an extremely rare malignancy of the placenta that is often associated with fetomaternal hemorrhage (FMH). This combination is challenging to diagnose antepartum and is associated with high perinatal mortality, predominantly due to severe fetal anemia.MethodsWe report a case of IC associated with FMH and conducted a systematic review of cases published in the English and Chinese literature. Data from these cases were combined to evaluate clinical characteristics, diagnostic approaches, treatment options, and outcomes.ResultsA 31-year-old woman presented with decreased fetal movements at 34 weeks and 2 days of gestation. Following an emergency cesarean section, the infant was found to be severely anemic and passed away shortly after delivery. The placental histopathology revealed IC. The patient received chemotherapy with EMA/CO and showed no evidence of metastasis or recurrence over 12 months of follow-up. The systematic review identified 35 cases of IC associated with FMH. Common diagnostic clues included decreased fetal movements, abnormal middle cerebral artery Doppler studies, and FMH. Despite the severe perinatal outcomes, maternal prognosis was generally favorable with chemotherapy in case of metastasis.ConclusionIC with FMH is a rare but life-threatening condition requiring high clinical suspicion and prompt placental histopathology for diagnosis. Early recognition of fetal anemia and FMH is essential for timely intervention.